2019
DOI: 10.13057/biodiv/d200614
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of caffeine-degrading bacteria from soil, coffee pulp waste and excreted coffee bean in Luwak feces

Abstract: Abstract. Iswanto T, Shovitri M, Altway A, Widjaja T, Kusumawati DI, Lisdiyanti P. 2019. Isolation and identification of caffeine-degrading bacteria from soil, coffee pulp waste and excreted coffee bean in Luwak feces. Biodiversitas 20: 1580-1587. The present study deals with the isolation and identification of caffeine-degrading bacteria obtained from the caffeine contaminated environment or caffeinated wastes. These bacteria are useful for various biotechnological applications especially in increasing the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…Recently, it was shown that CBB-associated P. fulva and other four Pseudomona species contains a full gene complement for caffeine metabolism, while other additional sixteen bacteria species contain partial gene complements for the same process (Vega et al, 2021). Caffeine degradation capability has been shown for other strains of Stenotrophomonas, Serratia, Acinetobacter, Klebsiella, Rhodococcus, and Methylobacterium as well (Madyastha and Sridhar, 1998;Yamaoka and Mazzafera, 1998;Iswanto et al, 2019). Bacteria in the genus Pseudomonas were shown to be highly abundant (21-25%) in CBB females from coffee plots in Puerto Rico (Mariño et al, 2018) but not in our study (1.1% in the CBB female sample).…”
Section: Figures 1amentioning
confidence: 99%
“…Recently, it was shown that CBB-associated P. fulva and other four Pseudomona species contains a full gene complement for caffeine metabolism, while other additional sixteen bacteria species contain partial gene complements for the same process (Vega et al, 2021). Caffeine degradation capability has been shown for other strains of Stenotrophomonas, Serratia, Acinetobacter, Klebsiella, Rhodococcus, and Methylobacterium as well (Madyastha and Sridhar, 1998;Yamaoka and Mazzafera, 1998;Iswanto et al, 2019). Bacteria in the genus Pseudomonas were shown to be highly abundant (21-25%) in CBB females from coffee plots in Puerto Rico (Mariño et al, 2018) but not in our study (1.1% in the CBB female sample).…”
Section: Figures 1amentioning
confidence: 99%
“…Klebsiella quasipneumoniae and Acinetobacter baumannii have been identified as member of Proteobacteria. Klebsiella quasipneumoniae had been successfully isolated from excreted coffee beans in Luwak feces (Iswanto et al 2019). Some species of Klebsiella has been reported to have cellulolytic and hemicellulolytic activity including K. pneumonia from digestive tract of Bombix morii (Anand et al 2010), K. ozeanae (Kalaiselvi and Jayalakshmi 2013), K. oxytoca, K. variicola (Dantur et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This strategy was successfully employed to demonstrate the ability of some biocontrol agents to inhibit the development of some of the major coffee diseases such as the CLR caused by the fungal pathogen H. vastatrix (Shiomi et al, 2006;Bettiol et al, 2007;Silva et al, 2008Silva et al, , 2012Daivasikamani and Rajanaika, 2009;Haddad et al, 2013) or the coffee wilt disease (CWD) also known as tracheomycosis caused by the fungal pathogen Gibberella xylarioides (Muleta et al, 2007;Mulaw et al, 2010Mulaw et al, , 2013Tiru et al, 2013). This methodology was also used to reveal the microorganisms biocontrol potential toward numerous other phytopathogens including Alternaria alternata, A. solani, Ambrosiella macrospora, Botrytis cinereal, Colletotrichum gloeosporioides, C. coffeicola, Fusarium oxysporum, F. solani, F. verticillioides, Glomerella sp., Macrophomina phaseolina, Myrothecium roridum, Pestalotia longisetula, Phoma sp., Phytophthora capsici, P. meadii, Pythium aphanidermatum, Rhizoctonia solani, and Sclerotinia sclerotiorum (Nair et al, 2002;Mulaw et al, 2013;Bongiorno et al, 2016;Kejela et al, 2016;Monteiro et al, 2017;Ranjini and Raja, 2019;Hoang et al, 2020;Duong et al, 2021) but also some pests such as the coffee berry borer Hypothenemus hampei (Vega et al, 2008), the root knot nematode Meloidogyne incognita (Mekete et al, 2009;Hoang et al, 2020), the burrowing nematode Radopholus duriophilus, and the root lesion nematode Pratylenchus coffeae (Duong et al, 2021), as well as some toxigenic fungi including Aspergillus carbonarius, A. flavus, A. niger, A. ochraceus, and A. westerdijkiae (Masoud and Kaltoft, 2006;Ramos et al, 2010;Djossou et al, 2011;Leong et al, 2014;De Melo Pereira et al, 2015a;De Almeida et al, 2019).…”
Section: Potential Uses As Biocontrol Agentsmentioning
confidence: 99%
“…However, these strategies are difficult to implement because of caffeine, tannin, and polyphenol contents that make the wastes toxic. For these reasons, microorganisms have also been studied for their potential utilization in detoxifying the coffee wastes and were therefore screened for their capacity to degrade the caffeine and tannins (Aquiahuatl et al, 1988;Roussos et al, 1995;Brand et al, 2000;Mazzafera, 2002;Nayak et al, 2012). Finally, microorganisms have also been explored for some industrial applications such as the production of enzymes with by-products such as amylases (Murthy et al, 2009), pectinases (Antier et al, 1993;Boccas et al, 1994;Sakiyama et al, 2001;Serrat et al, 2002;Masoud and Jespersen, 2006), proteases (Rodarte et al, 2011), and xylanases (Murthy and Naidu, 2012).…”
Section: Potential Uses As Biocontrol Agentsmentioning
confidence: 99%